Flora Ferroviária Paulista: diversidade vegetal, araneofauna associada e impactos dos empreendimentos ferroviários - Mendes, Zedenil Rodrigues (2023)
The flora that occurs along the railways has always caught my attention. While listening to other passengers refer to the plants seen from the windows as “weeds”, I always wondered how many and who are the species that grow along the tracks. The present study aims to make the knowledge of these species flourish for science and for people. There is not enough data in Brazil regarding the vegetation on railways as well as the potential ecosystem services offered by these species. To take an initial step in floristic research on railroads, I decided to study the flora of a tourist region in Paranapiacaba. The surveyed stretches cross different degrees of anthropic impact and are used, in part, for the transport of passengers and, in part, for the transport of cargo. It was possible to collect a satisfactory amount of data to evaluate the vegetation occurring on the railways. Data were also collected on the spider fauna present in some plant species that occur along the railroad. The study area was threatened by the construction of an undertaking that would deforest part of the preserved vegetation of the Atlantic Forest, since stretches of railway and highway would be duplicated. However, CETESB embargoed the work. Even so, the study is necessary and urgent, as new infrastructure projects can threaten a well-preserved area, where most of the population depends on ecological tourism. In the first chapter, a review of articles and academic publications on the flower in railways, most of them in Europe; The second 3chapter presents a study on the flora associated with spiders collected using different methods; In the third, we present an article that will be submitted to the FLORA journal. It presents data from four railway sections in operation; The fourth chapter brings data from the same stretches in activity along with data from an abandoned stretch of railroad, highway, roads, trails and a stretch of water course that cuts through the railroad; The fifth chapter includes a scientific initiation work under my guidance with a list of publications on the potential use of 100 species found in railroads.